Reconstructing Family Household Duties Based On Equality In Facing The Digital Technology Era - Ahdar; Musyarif; Moh. Zulkarnaen; Muh. Ilham Jaya; Ayunytyah Eka Wardani (Yayasan Zia Salsabila, 2025)
This study aims to analyze the reconstruction of household duties based on equality in facing the digital technology era. It employed a descriptive qualitative method with a phenomenological approach in Parepare City. The informants consisted of 13 participants, including three mothers/wives, two fathers/husbands, three children, and five women activists, PKK members, and community empowerment actors. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing or verification. The findings show that the division of household duties remains unequal because women continue to be the main actors responsible for domestic work, childcare, family needs management, and children’s digital supervision. Digital technology supports family life through communication, financial management, education, online shopping, and online business. However, it also creates new burdens, including digital demands, reduced face-to-face interaction, and increasing dependence on gadgets. Husbands’ and children’s involvement has begun to appear, but it remains limited and is often understood as assistance rather than shared responsibility. This study concludes that reconstructing household duties requires husband-wife partnership, equal involvement of children, family digital literacy, and community-based social support.